Clinical evaluation of silorane and nano-hybrid resin composite restorations in class ıı cavities up to 3 years - Öztürk Bozkurt, Funda; Toz, Tuğba; Kara Tuncer, Aysun; Gözükara Bağ, Harika; Özcan, Mutlu (Operative Dentistry, Inc., 2016)
In this study, the clinical performance of a silorane-based resin composite (SC) vs a nano-hybrid resin composite (NHC) was evaluated in Class II cavities. From January 2012 to February 2013, a total of 29 patients (eight men, 21 women; mean age, 24 +/- 5 years) received 29 pairs of restorations using both SC (Filtek Silorane, 3M ESPE) and NHC (Filtek Z550, 3M ESPE) materials. Patients were followed until February 2015. One operator performed all restorations using the corresponding adhesive resins according to the manufacturers' instructions. Two calibrated independent examiners evaluated the restorations at one week, six months, and then annually using the modified United States Public Health Service (USPHS) criteria for anatomic form, marginal adaptation, color match, surface roughness, marginal discoloration, secondary caries, and postoperative sensitivity. Changes in the USPHS parameters were analyzed with the McNemar test (alpha=0.05). The mean observation period was 31.2 months. Marginal adaptation was the only parameter that showed a significant difference and was worse for SC than NHC (p=0.012). At the final recall, 17 restorations from the SC group and five from the NHC group received a score of 1 (explorer catches). These scores were significantly different between baseline and final recall for SC (p<0.001) but not for NHC (p>0.05). Both NHC and SC performed similarly in Class II restorations up to three years except for marginal adaptation, for which the latter demonstrated significant deterioration at the final recall compared with baseline.
WOS: 000387340400004
PubMed ID: 27589274
Keywords: Clinical; Nano-Hybrid Resin Composite (NHC); Restorations